Type 2 diabetes mellitus non-lab pre-screening in schoolchildren aged 3-6 years in Eastern Amazon, Brazil - Silva, Alice Maria; Sena, Taiana Trindade; Jedlicka, Letícia Dias Lima; Carvalho, Aline Correa; Campos, Ana Cristina Viana (Brazilian Journal of Science, 2022)
Type 2 Diabetes mellitus is a chronic disease that affects more than 415 million people worldwide. Some risk factors to consider among children are poor diet, obesity, physical inactivity, family history, if the mother has been diagnosed with gestational diabetes mellitus and early weaning. Our objective was to propose a non-lab pre-screening test for Type 2 Diabetes mellitus among preschoolers aged 3 to 6 years old in the Amazon region, Maraba, Brazil. Our sample comprised (N=425) children enrolled in a public preschool and their respective caregivers/parents. A discriminant analysis was used to test the score’s ability to maximize the differences between groups according to the relation to the risk factors for Type 2 Diabetes mellitus. Our results suggested that our proposed pre-screening test for Type 2 Diabetes mellitus-using assessment of risk factors is as simple as statistically significant based on heredity, overweight/obesity, physical inactivity, and habit of intake high-calorie foods. The proposed pre-screening test for Type 2 Diabetes mellitus using assessment of risk factors is a simple as statistically significant method for potentially identifying children at risk for Type 2 Diabetes mellitus in schools.